Finding Home / Finding Resilience in-between the Writer / Director / Actor / Audience relationships. - Mercer, Leah (2016)
Depending upon whether you are thinking of the Borg from 'Star Trek' or the Vogon from the 'Hitchhiker’s Guide to the Galaxy', the old saying goes ‘Resistance is futile/useless’. Sometimes it is best to adapt, revise, regroup, move, bend, or change rather than resist. To remain relevant, vital and strong resilience is important. Resilience enables us to hang in there, to recover quickly, to rebuild and thrive. Sometimes the focus of our art/research/educational practices/sector is building resilience in others. Sometimes it is important to focus on building resilience within ourselves as individuals or in our communities of practice. Resilience implies a source of compression, a passage of time, and a process (or an innate ability) to spring back to a (positive) “normal” state.